Minimum interference strong bidirectional topology for wireless sensor networks. (30th July 2013) - Panda, B.S.; Shetty, D. Pushparaj
One of the critical constraints for lifetime and operability of sensor networks is the limited amount of available energy. Reducing the interference is one of the important positive steps towards this as high interference number increases the probability of packet loss and hence forces the sender node to retransmit the packets resulting in more energy consumption. Minimum Interference Strong Bidirectional Topology (MISBT) problem is to assign transmit power to each sensor in a sensor network such that the maximum/average node interference of a sensor is minimised subject to the constraint that the induced topology containing bidirectional links only is strongly connected. In this paper we propose two new models for measuring the interference, namely the MAX model and SUM model. We present algorithms for minimising maximum and average node interference under these models. The average interference obtained by our algorithms for MAX and SUM models is at most twice the optimal. The simulation results show that the total power consumptions by the solution produced by our algorithm under the SUM model is less than the solution produced by the existing algorithm under the OR model. Furthermore, our algorithms under different models are 2–approximation algorithms for the average receiver–centric interference as well.